First record of Scinax centralis (Anura, Hylidae) in the Triângulo Mineiro region, state of Minas Gerais, southeastern Brazil, with further data on its vocalization - Bang, Davi Lee; Pie, Marcio; Giaretta, Ariovaldo Antonio (Papéis Avulsos de Zoologia, 2021)
Scinax comprises more than 120 species which are split in two clades, the S. ruber and the S. catharinae clades. A few species within the S. catharinae clade occur in gallery forests of the Brazilian Cerrado. We here extend the distribution of S. centralis southwards based on new populations sampled in the banks of the Rio Paranaíba, in the borders of Minas Gerais (MG) and Goiás (GO) states, southeastern Brazil. We also provide further data on the species vocalization. Variation was seen among our population and topotypes regarding SVL and call dominant frequency, both likely representing a clinal variation. Our new population of S. centralis represents the first record of the species for the state of Minas Gerais.